Model Matematika Interaksi Glukosa-Insulin Dalam Tubuh Penderita Diabetes Tipe 1 - Nurma Yenni; Muhammad Subhan (Journal of Mathematics UNP, 2022)
Diabetes Mellitus (DM) is a metabolic disease caused by a lack of the hormone insulin. This disease is a non-communicable disease that causes death. Diabetes control measures are needed, especially trying to keep blood sugar levels as close to normal as possible. This research is a basic or theoretical research. This study begins by determining the variables, assumptions, and parameters related to the problem so that a mathematical model of the glucose-insulin interaction in the body of type 1 diabetes patients can be formed. one equilibrium point. Then the stability of the equilibrium point is seen based on the eigenvalues of the Jacobi matrix, which shows that all the eigenvalues are negative, so that the equilibrium point of the mathematical model of glucose-insulin interaction in the body of type 1 diabetics is asymotic stable. This shows that diabetes will not disappear from the sufferer's body. The results of the numerical simulation also strengthen the analysis that has been carried out.